Review: Factors Relating to Nurses’ Caring Behaviors for Dying Patients - Prompahakul, Chuleeporn; Nilmanat, Kittikorn (Nurse Media Journal of Nursing, 2011)
Background: Nowadays, caring for patients at the end of life becomes an indicator of the quality of care in a hospital. Nurses are the key people to provide care for dying patients, therefore caring behaviors of nurses could affect the quality of care. To attain and maintain the quality of care at the end of life, factors that contribute to nurses’ caring behaviors for dying patients needs to be addressed.Purpose: The purpose of this article is to review factors relating to nurses’ caring behaviors for dying patients from existing literature.Method: Relevant literature from electronic databases, including CINAHL, PubMed, Science direct, OVID, Proquest, and The Cochrane Library during the year 1990-2010, was examined, synthesized, and categorized systematically.Result: The results showed that factors related to a nurse’s caring behavior for a dying patient can be classified into three groups. These include; Nurse’s personal factors, Technological influencing factors and Environmental factors.Conclusion: The three factors related to nurses’ caring behaviors for dying patients in the current review could serve as a valuable database to implement in nursing practice, education and research, in order to achieve quality of end-of-life care.Key words: caring behavior, relating factor, dying patient